2013
DOI: 10.1152/ajpcell.00345.2012
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin abates hypoxia-induced oxidative stress based-ER stress-mediated cell death in mouse hippocampal cells (HT22) by controlling Prdx6 and NF-κB regulation

Abstract: Oxidative stress and endoplasmic reticulum (ER) stress are emerging as crucial events in the etiopathology of many neurodegenerative diseases. While the neuroprotective contributions of the dietary compound curcumin has been recognized, the molecular mechanisms underlying curcumin's neuroprotection under oxidative and ER stresses remains elusive. Herein, we show that curcumin protects HT22 from oxidative and ER stresses evoked by the hypoxia (1% O(2) or CoCl(2) treatment) by enhancing peroxiredoxin 6 (Prdx6) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 101 publications
10
91
0
Order By: Relevance
“…Quantitation by H 2 -DCF-DA dye (13,25) demonstrated that Prdx6 acted to protect cells by reducing their oxidative load (Fig. 2C, black bar vs. gray bar).…”
Section: Loss Of Prdx6 In Hcn-2 Neuronal Cells During Oxidative Stresmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantitation by H 2 -DCF-DA dye (13,25) demonstrated that Prdx6 acted to protect cells by reducing their oxidative load (Fig. 2C, black bar vs. gray bar).…”
Section: Loss Of Prdx6 In Hcn-2 Neuronal Cells During Oxidative Stresmentioning
confidence: 99%
“…Absorbance was measured at 405 nm using a microtiter plate ELISA reader. Transactivation activities were adjusted for transfection efficiencies using GFP/SEAP values (13,23).…”
Section: Expression and Purification Of Tat-ha-prdx6 Recombinant Protmentioning
confidence: 99%
See 3 more Smart Citations